The Effect of Dividend Income Taxes on Equity Market Transaction Volume: The Case of OECD Countries - Karakas, Mesut (MALIYE BAKANLIGI, 2021)
In this study, the effect of the cumulative tax rate on the dividend income on the stock market transaction volume is examined with the panel-ARDL approach by considering the 2000-2019 period for OECD countries. Findings show the effect of taxes and trade openness is negative in the longrun, but the effect of real interest rates is positive. In the short-run, the effect of taxes is negative, while the effect of real gross domestic product per capita and trade openness is positive. The reduction of taxes on dividend income will contribute to financial development by increasing the stock market transaction volumes.
Keywords: Tax; Dividend Income; Financial Markets and Institutions; FINANCIAL DEVELOPMENT; PANEL COINTEGRATION; DETERMINANTS; INFLATION; INSTITUTIONS; TESTS; GLOBALIZATION; CAUSALITY; OPENNESS; GROWTH; Business & Economics